Manajemen Komunikasi Islam Camat Maiwa dalam Meningkatkan Kedisiplinan Pegawai di Kabupaten Enrekang - Suhriati, Suhriati; Qadaruddin, Muhammad; Iskandar, Iskandar; Nurkidam, A.; Ramli, Ramli (IAIN Padangsidimpuan, 2023)
This research discusses the Islamic communication management of Maiwa District Head in Improving Employee Discipline in Enrekang Regency. The aim is to describe the level of employee discipline, the Islamic communication management of Maiwa District Head and the impact of the Islamic communication management implemented by Maiwa District Head. This type of research is descriptive qualitative research characterized by field research. The informants in this study are the Maiwa District Head and his staff and the community within the Maiwa district. Data collection techniques through observation, interviews and documentation. The results of this study indicate that: 1) The level of employee discipline in the Maiwa District Office, in accordance with Max Weber's theory of social action, where actions are based on habits, emotional conditions, rational and values that contain mutual benefits; 2) Islamic communication management applied by Maiwa District Head in improving the discipline of its employees, in accordance with Barbara O'Keefe's message logic theory, where the message design technique is based on expressive logic, conventional and good rhetoric; 3) The impact of communication management applied by Maiwa District Head in improving employee discipline is; a) increased discipline; b) effective and harmonious communication; c) peaceful, safe and prosperous; d) motivated and; e) self-confidence. Through this research, it is known that leadership communication management is very influential on the level of discipline, self-confidence and employee morale